HUBUNGAN PENGETAHUAN DAN SIKAP IBU POST PARTUM PRIMIPARA TENTANG CARA MENYUSUI DENGAN PRAKTIK IBU MENYUSUI DI RUANG BAITUNNISA RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Kurnia Yuli Astanti; Maya Dwi Yustini (Universitas Muhammadiyah Semarang, 2013)
The problem in the suckling practice usually refer to lack of understanding and behavior from Post Partum Primipara mother whics will affect to the mother’s awareness. The suckling practice is not just pop-up reflectifely but it has to go through the information and practice on how to do the suckling correctly.This research head for knowing the relationship between the knowledge and behavior of post partum primipara mother on the method and practice of suckling.This research type is descriptive with the correlation study and cross sectional and observation approach. This research involved 21 responden of post partum primipara mother at Baitunnisa room on April 2009. Data processing and analysis is done with computer by using PearsonCorelation program to get the relationship between 2 variables. In this research, there are 9 respondens (42.9 %) who had well knowledge, good/participative behavior and well practice on suckling. And refer to the statistic data, it shows correlation number of 0.644, significant correlation number of 0.002 with research significant number of 0.05 for the knowledge variable for post partum primipara mother on the method and practice of suckling. And it shows correlation number of 0.831, significant correlation number of 0.000 with significant research number of 0.05 for the behavior variable of post partum primipara mother on the practice and method of sucking. From those statistic results, it concluded there is significant and strong relationship between knowledge of post partum primipara mother on the practice and method of suckling. Keywords: Knowledge, Behavior, Suckling Practice.